2022
DOI: 10.1136/bmjopen-2021-053277
|View full text |Cite
|
Sign up to set email alerts
|

Stated preferences for family doctor contract services: a survey of the rural elderly in Anhui Province, China

Abstract: ObjectiveA number of factors contribute to the utilisation of family doctor contract services (FDCS) in China. This study aims to measure the preferences of the elderly for the FDCS and identify the key factors (and their relative importance) that may guide policymakers in more accurately providing the FDCS.Participants and methodsA discrete choice experiment was performed to elicit the preferences for FDCS among the rural elderly in China. Attributes and levels were established based on qualitative methods. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…The empirical analysis in this study reveals that improving the service quality of medical institutions and standardizing the diagnosis and treatment process not only enhances patients' trust in medical services, but also deepens their reliance on primary care. This finding is consistent with previous research findings that suggest that good organizational structure and processes can increase user satisfaction and dependence 39 43 . It is worth noting that although the physical condition of healthcare facilities and the modernization of equipment had an effect on patient attraction, this effect was not significant in this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The empirical analysis in this study reveals that improving the service quality of medical institutions and standardizing the diagnosis and treatment process not only enhances patients' trust in medical services, but also deepens their reliance on primary care. This finding is consistent with previous research findings that suggest that good organizational structure and processes can increase user satisfaction and dependence 39 43 . It is worth noting that although the physical condition of healthcare facilities and the modernization of equipment had an effect on patient attraction, this effect was not significant in this study.…”
Section: Discussionsupporting
confidence: 93%
“…In short, having better physicians will more effectively direct the flow of patients to primary healthcare. In addition, a good family doctor system has been shown to be positively associated with better health outcomes and lower healthcare costs 38 , 39 . Tianjin has taken the lead in developing family doctor contracting services since the policy's implementation, and the contracting rate has reached a high level.…”
Section: Theoretical and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the elderly with MCCs have a higher demand for health services and may be more likely to contract with family doctors. Wang's study showed that the elderly want family doctors to provide more chronic disease management services [ 22 ]. Yang's study found that the elderly with cardiovascular-metabolic multimorbidity were more willing to contract with family doctors.…”
Section: Introductionmentioning
confidence: 99%